Ameloblastic Carcinoma of Mandible: Facts and Dilemmas. Issue 5 (September 2014) - Dutta, Mainak; Kundu, Sohag; Bera, Himel; Barik, Sabyasachi; Ghosh, Bhaskar
Ameloblastic carcinoma is a rare malignant odontogenic tumor and is considered as the malignant counterpart of ameloblastoma with features of both benign and malignant histology. It may arise de novo or from a long-standing ameloblastoma and is locally aggressive with a propensity for metastasis. With limited documentation, little is known about its pathobiogenesis, with no universal guidelines for management. For clinicians, differentiating ameloblastic carcinoma from ameloblastoma and malignant ameloblastoma in a patient presenting with a suspicious jaw tumor is a challenge due to overlapping clinical features, inconclusive cytology/biopsy reports, different management approaches and inadequate follow-up. Proper knowledge of the disease entity and a high index of suspicion are essential. Here we elaborate the dilemmas in diagnosis and management of ameloblastic carcinoma through presentation of a representative case in a 56-year-old man presenting with a tumor in the mandible.